Representasi Pemberontakan Perempuan Pada Novel “Kasta” Karya Witri Prasetyo Aji dan Novel “Kenanga” Karya Oka Rusmini - Rahmah, Aulia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In general, everyone has the right to choose a partner according to their wishes. However, the problem is that in Bali there is still a strong caste system. This triggers the rebellion of Balinese women in the novel Kasta and Kenanga. This study aims to describe the forms of rebellion perpetrated by women of the Balinese Brahmin caste from the two novels. The data analyzed in this study are part of the text of the two novels. The results of the research show that the female characters in both novels wish to live freely without being bound by the caste system.